Indigenous identity elements from community self-management in the times of COVID-19 pandemic: the young volunteer shipibos of the Matico Command - Balvín Bellido, Sandra (2021)
With the many human losses brought about by the health emergency caused by the COVID-19 and state abandonment, a group of young Shipibo from Yarinacocha - Pucallpa formed a voluntary group called Comando Matico, to face this emergency based on ancestral Shipibo medicine. These young ones decide to act despite state restrictions, motivated by what seems to be an ancient-rooted solidarity among the Shipibo. This article explores the identity construction of the group, which performs a series of convening practices to obtain the support of the virtual community for its voluntary work and citizen demand from the State, intermixed and sustained in particular forms of self-representations in Facebook´s virtual space. This construction for practical purposes in virtuality (oriented, as we have been mentioning, to indigenous self-management) is intimately linked to the process of offline identity construction. The pandemic context, is conducive to a renewal of the implementation of ancestral shipibo knowledge; as well as, for the young volunteers that resume the search for recognition of their ancestral heritage, nurturing the referred process of identity construction at the same time that it strengthens the search for indigenous autonomy –at least with regard to the field of health.